2021
DOI: 10.1161/strokeaha.120.032390
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Monitoring of Intracranial Pressure After Decompressive Craniectomy in Malignant Stroke

Abstract: Background and Purpose: The role of decompressive hemicraniectomy (DC) in malignant cerebral infarction (MCI) has clearly been established, but little is known about the course of intracranial pressure (ICP) in patients undergoing this surgical measure. In this study, we investigated the role of invasive ICP monitoring in patients after DC for MCI, postulating that postoperative ICP predicts mortality. Methods: In this retrospective observational study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Hence, despite both thresholds of 7 and 11 mmHg are traditionally considered “low-normal”, if not attained, the likelihood of the progressive swelling leading to difficulties in controlling ICP at its peak, around day two to five after stroke ( 49 , 50 ), is substantial. Furthermore, there is some evidence that the postoperative target for malignant cerebral infarctions should be lower than the 20 mmHg commonly used in traumatic brain injuries ( 37 , 51 , 52 ), further lending credence to the notion that a lower ICP target should be the goal. In addition, the similar rates of re-operation and syndrome of the trephine amongst both groups demonstrates that further decompression to “low-normal” ICP targets is safe and well tolerated by patients.…”
Section: Discussionmentioning
confidence: 94%
“…Hence, despite both thresholds of 7 and 11 mmHg are traditionally considered “low-normal”, if not attained, the likelihood of the progressive swelling leading to difficulties in controlling ICP at its peak, around day two to five after stroke ( 49 , 50 ), is substantial. Furthermore, there is some evidence that the postoperative target for malignant cerebral infarctions should be lower than the 20 mmHg commonly used in traumatic brain injuries ( 37 , 51 , 52 ), further lending credence to the notion that a lower ICP target should be the goal. In addition, the similar rates of re-operation and syndrome of the trephine amongst both groups demonstrates that further decompression to “low-normal” ICP targets is safe and well tolerated by patients.…”
Section: Discussionmentioning
confidence: 94%
“…Certainly, future research studies should aim to investigate the neurological sequelae of external pressure on the unprotected brain. In the acute setting, ICP monitoring would be a valuable outcome measure that is already widely used for these patients ( 11 , 12 ). Correlation of ICP at the time of observed craniectomy site contact in a prospective study would provide a truer estimation of transmitted interface pressure.…”
Section: Resultsmentioning
confidence: 99%
“…Sang beom Jeon et al [ 18 ] analyzed the changes of ICP within 24 hours after DC, they concluded that early evaluation of ICP changes and effective intervention can improve the prognosis of patients. Silvia Hern á ndez dur á n et al [ 19 ] concluded that a threshold of 10 mmHg within the first 72 positive hours was a reliable predictor of mortality in MCI, with an acceptable sensitivity of 70% and high specificity of 97%. However, at present, there are few studies on the changes of ICP within 1 week after DC.…”
Section: Discussionmentioning
confidence: 99%